Zoroastrian Scholasticism in late antiquity : The Pahlavi version of the Yasna Haptaŋhāiti - Zeini, Arash (Edinburgh studies in ancient Persia., 2020)
Zeini challenges the view that considers the Zand's study an auxiliary science to Avestan studies, framing the text instead within the exegetical context from which it emerged.